Juvenile Panhypopituitarism in a Dog – What are the Therapeutic Challenges? - Vargas, Alessandra Martins; Santos, André Luís Soares dos; Gouvêa, Fernanda Nastri; Pennacchi, Caio Santos; Crivellenti, Leandro Zuccolotto; Borin-Crivellenti, Sofia (Acta Scientiae Veterinariae, 2022)
Background: Juvenile panhypopituitarism is an endocrinopathy that affects young dogs and must be differentiated from other causes of height disorders, as one could have a deficiency of one or more adenohypophysis hormones, besides growth hormone. Diagnosis consists of excluding endocrine and non-endocrine causes. Treatment requires administration of heterologous porcine growth hormone or progestins, as well as supplementing other hormones that are deficient in the circulation. The prognosis for these patients tends to be unfavorable and they have a shorter life expectancy. The present case aimed to report the therapeutic challenges in a dog diagnosed with juvenile panhypopituitarism. Case: This study presents the case of a 6-month-old crossbred Labrador/Brazilian Fila dog, not neutered, 6.7 kg of body weight (body condition score 5/9), with a growth disorder and persistence of the puppy coat, when compared to other members of the same litter. During inspection, it was possible to observe an undersized dog and soft puppy coat, besides no bone irregularities or joint tenderness was noted. The other physical examination parameters were within the normal range for the species. No changes in complete blood count and only increases in urea, cholesterol and alkaline phosphatase activity were observed. Thyroid and abdominal ultrasound (US) examination did not reveal any remarkable changes. After serum dosage of insulin-like growth factor, thyroxine, thyrostimulating hormone, and cortisol, the patient was diagnosed with juvenile panhypopituitarism and underwent therapy with medroxyprogesterone and thyroid hormone supplementation. Monitoring was instituted at intervals of 3, 6, and 12 weeks, and currently every 3 or 4 months and the IGF-1 values normalized after 6 months with. After 8 months of therapy, the patient had good body growth and bone mineralization compared to the time of diagnosis. However, skeletal development was completed only 12 months after hormone replacement, accompanied by the presence of vertebral osteophytes and coxofemoral osteoarticular alterations. Considering chronic use of progestins, ovariosalpingohysterectomy (OSH) was recommended, but for personal reasons, the owners chose to do not submit her to surgery. After 18 months of treatment, the dog starts to exhibit prostration, selective appetite, and increased abdominal volume. After imaging exam, she was forwarded for OSH, due to consistent findings of pyometra. Subsequently, even the supervision of possible comorbidities involved in the chronic use of progestins was maintained at half-yearly intervals, the bitch returned to the service with skin thickening, increased limb volume, and macroglossia after 60 months of therapy. At this point IGF-1 values were higher when compared to the previous measurements and the application of medroxyprogesterone was suspended. Its supplementation was reintroduced only after 8 months when IGF-1 was significantly reduced. To date, the patient is close to 6 years of age and with a good quality of life. Discussion: The greatest therapeutic challenge for these patients involves dealing with the adverse effects of progestins, mainly related to reproductive disorders and alopecia at the application site, as well as maintaining adequate hormone replacement in order to avoid hypersomatotropism. Although longevity is lower in these individuals, the patient in this report has achieved six years of age and has had an excellent quality of life so far. Keywords: adenohypophysis, growth hormone, pituitary dwarfism, thyrostimulating hormone.